Two views on language ecology and ecolinguistics. (March 2016) - Kravchenko, A.V.
Abstract: It is shown that the definition of the subject area of Haugenian ecolinguistics is methodologically inconsistent because of the implicit biomorphic metaphor, the language myth, and indiscrimination between the two different approaches to language known as cognitive internalism and cognitive externalism. A more consistent definition of language ecology is given, based on the biology of cognition as a theory of the living; consequently, the subject area of ecolinguistics is defined differently, with a focus on the nature and function of language as a mode of organization of the living system (society) and its role in the development of the brain, mind, and (self-)consciousness. Highlights: Linguistics often misconstrues its object of study by reifying language. The phenomenon of language is grounded in human biology. The biology of language is best explained by the theory the living. This theory calls for a different understanding of language ecology. The subject of ecolinguistics should be the nature and function of language as a mode of organization of the human living system.